1990
DOI: 10.1002/mrd.1080260111
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an increased sensitivity to Ca2+ in the flagella of sperm from tw32/+ mice

Abstract: The majority of sperm from mice carrying the tw32 haplotype undergo hyperactivation sooner than sperm from +/+ mice of the same strains (Olds-Clarke, Dev Biol 131:475-482, 1989). To investigate the mechanism underlying this abnormal motility, the Ca2+ sensitivity of their flagellar apparatus was compared to that of age- and strain-matched controls using Triton X-100-extracted sperm. Under these conditions, the curvature of the sperm flagellum is controlled by the free calcium concentration. Sperm from mice car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…By using the asymmetrical hook on the head of mouse sperm as a reference for the direction of the flagellar bend, we were able to identify two distinct kinds of asymmetrical beating. Procaine [24,[29][30][31][32], 4-AP [33,34], and thimerosal [21] are reported to trigger hyperactivation in the sperm of humans, guinea pigs, and cattle, but the response to thimerosal might actually be the reverse of the response to procaine and 4-AP.…”
Section: Discussionmentioning
confidence: 94%
“…By using the asymmetrical hook on the head of mouse sperm as a reference for the direction of the flagellar bend, we were able to identify two distinct kinds of asymmetrical beating. Procaine [24,[29][30][31][32], 4-AP [33,34], and thimerosal [21] are reported to trigger hyperactivation in the sperm of humans, guinea pigs, and cattle, but the response to thimerosal might actually be the reverse of the response to procaine and 4-AP.…”
Section: Discussionmentioning
confidence: 94%
“…This is likely the explanation for the phenomenon of calcium arrest that has been observed in many types of cilia and flagella when subjected to high Ca 21 after demembranation and reactivation (Walter and Satir, 1978;Gibbons and Gibbons, 1980). Ca 21 arrest has been observed and studied with reactivated rat and mouse sperm (Lindemann and Goltz, 1988;Lindemann et al, 1990). The force exerted to maintain the arrest configuration has been shown to be generated by dynein (Lindemann et al, 1992;Moritz et al, 2001), but the absence of switching suggests that it is generated by a subset of dyneins that are constitutively activated in the presence of high Ca 21 .…”
Section: When Functional Anatomy Meets Physiologymentioning
confidence: 92%
“…It was demonstrated that the response to Ca 2ϩ at high concentration leads to the arrest of flagellar beating at one extreme of the beat cycle. This produces candy-cane-shaped arrested flagella in sea urchin sperm [Gibbons, 1980;Gibbons and Gibbons, 1980] and fishhook-shaped arrested flagella in rat and mouse sperm [Lindemann and Goltz, 1988;Lindemann et al, 1990], as seen in Figure 1. Cilia also show arrest of the beat cycle in response to Ca 2ϩ [Satir, 1975;Satir et al, 1976], and the "hands up" arrest pattern is surprisingly similar to the fishhook of rat sperm [Satir et al, 1991].…”
Section: Introductionmentioning
confidence: 93%